2008
DOI: 10.1590/s0100-46702008000200001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some properties of 2,3 - and 3,4 - dimethoxybenzoates of Cu(II), Co(II) and Nd(III)

Abstract: The physicochemical properties of 2,4-, and 3,4-dimethoxybenzoates of Cu(II), Co(II) and Nd(III) were studied and compared to observe the-OCH 3 substituent positions in benzene ring on the character of complexes. The analysed compounds are crystalline hydrated or anhydrous salts with colours depending on the kind of central ions: blue for Cu(II), pink for Co(II) and violet for Nd(III) complexes. The carboxylate groups bind as monodentate, bidentate bridging or chelating and even tridentate ligands. Their therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The IR spectroscopy for the Cu(II) complex and for sodium salt of 4-nitrocinnamic acid and spectroscopic criteria [36,37] indicated that COOgroup coordinates monodently to the metal cation. XAFS studies confirmed the coordination via COOgroups and specified that the polyhedron of Cu(II) exhibits a square-planar geometry (CuO 4 ) with two carboxylate ligands coordinating in the monodentate mode and two aqua ligands (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The IR spectroscopy for the Cu(II) complex and for sodium salt of 4-nitrocinnamic acid and spectroscopic criteria [36,37] indicated that COOgroup coordinates monodently to the metal cation. XAFS studies confirmed the coordination via COOgroups and specified that the polyhedron of Cu(II) exhibits a square-planar geometry (CuO 4 ) with two carboxylate ligands coordinating in the monodentate mode and two aqua ligands (Fig.…”
Section: Discussionmentioning
confidence: 99%